Market Entry strategy of Interbev UK Ltd. Into the markets of Singapore and Malaysia - Shetty, Kunal (2012)
With a constant GDP rise in both Singapore and Malaysia the markets in these countries provide immense potential for foreign businesses. The idea of this report is to formulate an internationalization strategy for Interbev UK Ltd, a international beverage trading company in to the markets of Malaysia and Singapore. Interbev wants to enter the market via export and start dealing with the local distributors as an initial step towards being established in the region. The report examines various factors that are vital for Interbev to consider before entering these markets. It includes literature works on aspects such as selecting the mode of entry, exporting, market segmentation, targeting, positioning and country of origin effect. The dissertation poses two major questions i.e. segmenting the markets of Singapore and Malaysia & feasibility of exporting as a mode of entry. With the help of primary research (interviews, discussion and shelving observations) and secondary data (Government websites, Passport GMID and EuroMonitor reports) it attempts to answer the two major questions. The methodology involves personal visits to probable distributors, bars and retail in both the countries. The data analysis section interprets the data and puts into perspective the key factors to be considered whilst entering the two countries with current limitations present. Finally the report provides both short and long term recommendations for Interbev to enter the markets effectively